Multiple Description Coding with Redundant Expansions and Application to Image Communications. (19th February 2007) - Radulovic, Ivana; Frossard, Pascal
Abstract : Multiple description coding offers an elegant and competitive solution for data transmission over lossy packet-based networks, with a graceful degradation in quality as losses increase. In the same time, coding techniques based on redundant transforms give a very promising alternative for the generation of multiple descriptions, mainly due to redundancy inherently given by a transform, which offers intrinsic resiliency in case of loss. In this paper, we show how partitioning of a generic redundant dictionary can be used to obtain an arbitrary number of multiple complementary, yet correlated, descriptions. The most significant terms in the signal representation are drawn from the partitions that better approximate the signal, and split to different descriptions, while the less important ones are alternatively distributed between the descriptions. As compared to state-of-the-art solutions, such a strategy allows for a better central distortion since atoms in different descriptions are not identical; in the same time, it does not penalize the side distortions significantly since atoms from the same partition are likely to be highly correlated. The proposed scheme is applied to the multiple description coding of digital images, and simulation results show increased performances compared to state-of-the-art schemes, both in terms of distortions and robustness to loss rate variations.